Exploring post-divorce experiences : how children manage their interpersonal relationships and their self - Pah, Zhi Xin (2013)
Divorce rates in Singapore have been increasing in the recent years. It had increased from 6904 in 2006 to 7604 in 2011. Even though divorce is a serious social issue in Singapore, there is little information available on the experiences of divorces of children, especially that of young adults as most literature focused on post-divorce experiences of adolescents and young children. This paper hence, aims to explore the post-divorce experiences of children from divorced families, who are 21 and above and how they manage their interpersonal relations and selves as a result. The findings on the experiences of ten children who come from divorced families highlight some interesting recurring themes. These themes include the positive relationships with family members with closer ties to custodial parents, positive management of relationship with extra-familial members, a more tolerant view towards divorce as a solution to end unhappy marriages and reconstruction of self.